Transformative conversations about sexualities pedagogy and the experience of sexual knowing - Trimble, Lisa (Sex Education : Sexuality, Society and Learning, 2009)
One of the hallmarks of sex education traditionally has been its Cartesian endorsement of mind/body dualism; we have preferred to equate ‘self’ as synonymous with ‘mind’, and have invested heavily in believing in the valence of rationality‐based sexualities education. We generally do not consider the way ‘self’ negotiates, interprets and relates to sexual knowledge in all of our complexity, including our messy, embodied and emotional lives. In this paper I address what I think are several much‐needed conversations for a holistic pedagogy of sexualities to incorporate, including the falseness of the mind/body split, reconsidering what counts as sexual knowledge, the role of the performative in communicating our sexual knowing, and the importance of considering affect in learning about sexualities. The second part of the paper examines pedagogical considerations currently absent in dialogues of sexualities education, such as incorporating transformational learning strategies in teaching sexualities, and what it means to educate toward being a sexual citizen. Finally, I will outline how discussions of epistephenomenology (our relationship to and how we experience knowledge) can contribute to moving toward a vision of a critical, cultural sexualities education.
Number: 1
Keywords: approches et analyses; corps; discipline; discours dominant; phénoménologie; ressource en ligne; savoir expérientiel; science de l'éducation; sciences humaines; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; émotions; épistémologie